Stratification of lymph node metastases as macrometastases, micrometastases, or isolated tumor cells has no clinical implication in patients with cervical cancer: Subgroup analysis of the SCCAN project - Dostálek, Lukáš; Benešová, Klára; Klát, Jaroslav; Kim, Sarah H; Falconer, Henrik; Kostun, Jan; Dos Reis, Ricardo; Zapardiel, Ignacio; Landoni, Fabio; Ortiz, David Isla; van Lonkhuijzen, Luc R C W; Lopez, Aldo; et al. (Gynecologic oncology, 2023)
BACKGROUND: In cervical cancer, presence of lymph-node macrometastases (MAC) is a major prognostic factor and an indication for adjuvant treatment. However, since clinical impact of micrometastases (MIC) and isolated tumor-cells (ITC) remains controversial, we sought to identify a cut-off value for the metastasis size not associated with negative prognosis. METHODS: We analyzed data from 967 cervical cancer patients (T1a1L1-T2b) registered in the SCCAN (Surveillance in Cervical CANcer) database, who underwent primary surgical treatment, including sentinel lymph-node (SLN) biopsy with pathological ultrastaging. The size of SLN metastasis was considered a continuous variable and multiple testing was performed for cut-off values of 0.01-1.0 mm. Disease-free survival (DFS) was compared between N0 and subgroups of N1 patients defined by cut-off ranges. RESULTS: LN metastases were found in 172 (18%) patients, classified as MAC, MIC, and ITC in 79, 54, and 39 patients, respectively. DFS was shorter in patients with MAC (HR 2.20, P = 0.003) and MIC (HR 2.87, P < 0.001), while not differing between MAC/MIC (P = 0.484). DFS in the ITC subgroup was neither different from N0 (P = 0.127) nor from MIC/MAC subgroups (P = 0.449). Cut-off analysis revealed significantly shorter DFS compared to N0 in all subgroups with metastases ≥0.4 mm (HR 2.311, P = 0.04). The significance of metastases <0.4 mm could not be assessed due to limited statistical power (<80%). We did not identify any cut-off for the size of metastasis with significantly better prognosis than the rest of N1 group. CONCLUSIONS: In cervical cancer patients, the presence of LN metastases ≥0.4 mm was associated with a significant negative impact on DFS and no cut-off value for the size of metastasis with better prognosis than N1 was found. Traditional metastasis stratification based on size has no clinical implication.
Keywords: lymfatické uzliny; Macrometastasis; sentinelová uzlina; Lymph Nodes; Uterine Cervical Neoplasms; Neoplasm Staging; nádory děložního čípku; Disease-free survival; Histopathological ultrastaging; Sentinel lymph node; Low volume metastasis; Classification; nádory prsu; biopsie sentinelové lymfatické uzliny; Neoplasm Micrometastasis; Lymphatic Metastasis; Micrometastasis; Isolated tumor cells; lidé; ženské pohlaví; Breast Neoplasms; Humans; Cervical cancer; Prognosis; lymfatické metastázy; Female; staging nádorů; mikrometastázy; Sentinel Lymph Node Biopsy; Sentinel Lymph Node